Cuidado centrado à pessoa idosa institucionalizada com demência: teoria de médio alcance de enfermagem - Venturini, Larissa (2021)
The care of elderly people with dementia who reside in Long-Term Institutions for the Elderly (nursing homes - NH) is generally shown to be fragmented and does not consider subjective or individual aspects. It is understood that to provide quality care that has repercussions on the lives of elderly people living in these spaces, it is necessary to rethink the relationship between people and the services that take care of them, including the actions of nursing, a profession that performs care practices in these institutions. Thus, it was recognized in the perspective of Carl Rogers, through his theory of the Person-Centered Approach, foundations for possible (re)configurations of nursing care. In the meantime, the research question that guided this study was: what theoretical relationships can be established between Carl Rogers' Person-Centered Approach and nursing care for institutionalized elderly people with dementia in order to establish a mid-range theory? And as a general objective: to develop a medium-range theory for nursing care to institutionalized elderly people with dementia, supported by the Person-Centered Approach by Carl Rogers. In order to respond to the objective of this study, a prescriptive theoretical study was developed, focusing on the theoretical derivation strategy for the development of a mid-range nursing theory. In order to describe the phenomenon of nursing care for institutionalized elderly people with dementia, an integrative literature review was used as a method of synthesis. To “unpack” the knowledge put into Carl Rogers' theory, the construction of Gowin's V was developed. The derivation of concepts was developed to retranslate to nursing the concepts of the Person-Centered Approach, which were derived as: individual experience of the elderly person; experience for personal development; connections experience; experience for responsive congruence to reality; experience for choices; empathic experience and positive experience. The operationalization of the synthesis of statements made it possible to highlight the relational statements of the theory and to understand the seven nursing experiences necessary for the performance of care centered on elderly people with dementia in ILPIs as dependent and contextualized structures. Thus, it can be understood that nursing care for institutionalized elderly people with dementia, for it to develop in a focused way, it is necessary to incorporate the seven experiences. It is understood that the seven experiences require the nursing professional to recognize care as dependent on an individual, interactive, contextual, engaged, understanding, qualified perspective, which are linked to the biopsychosocial and theoretical-scientific skills of nursing professionals. It is inferred that from these experiences, elderly people with dementia, influenced by the characteristics and regulations of the NH, may benefit from a perspective of centered care. In addition, the operationalization of the Nursing Process and the development of nursing interventions based on the developed mid-range theory were established. It is believed that the development of this theory generates actions centered on the person, which can allow a re-dimensioning of the practices developed by nursing for elderly people with dementia in NH.